Replanning of The Wedi Irrigation Network System, Kapas District, Bojonegoro District - Mushthofa, Mushthofa; Indriani, Yulia; Riyadi, Andy Yanuar Putra (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Kapas District is located in Bojonegoro Regency with an area of ​​2,927 ha of rice fields and 2,805 ha of irrigation land. The obstacle faced by farmers is the uneven availability of irrigation water. The irrigation area in Wedi Village is still simple irrigation by pumping river water next to it. This research aims to plan the irrigation network in Wedi, by calculating irrigation water needs and planning the dimensions of the irrigation channels. The algebraic method is used to calculate rainfall and calculate water needs using the Net Field Requirements (NFR) system. Water requirements at the beginning of planting in November I obtained a maximum value of 1.79 lt/s/ha, the alternative for beginning of planting in December I obtained a maximum value of 1.90 lt/s/ha, and the alternative for beginning of planting in December II obtained a value of 1.88 lt/s/ha. Results of overall water balance analysis for each month in 1 year with 3 alternative plantings with surplus results. The channel dimensions obtained are SP 1 = 1.4 m x 1 m, SP 2 = 1.4 m x 1 m, SP 3 = 1.2 m x 1 m, SP 4 = 1.2 m x 1 m, and for secondary channels the results are SS 1 = 0.6 m x 1 m , SS 2 = 0.8 m x 1 m, SS 3 = 0.6 m x 1 m , SS 4 = 0.6 m x 1 m = , SS 5 = 0.6 m x 1 m. Keyword: Network Planning, Plant_water_requirements, NFR, channel dimensions.